Difficult Airway Management in Severe Tracheal Deviation Due to Large Nodular Goiter: A Case Report - I Wayan Eka Putrawan; I Made Gede Widnyana (Journal of Social Research, 2025)
Difficult airway remains one of the major challenges in anesthesiology practice due to its direct impact on perioperative morbidity and mortality. It is defined as a clinical situation in which there is difficulty with face mask ventilation, tracheal intubation, or both, even when experienced personnel and appropriate equipment are available. A 53-year-old female underwent an elective total thyroidectomy for a large goiter causing significant tracheal deviation to the left and restricted neck mobility. A neck CT scan revealed a markedly enlarged right thyroid lobe with tracheal deviation to the left. This condition has the potential to cause obstruction and difficult to ventilate during relaxation. Based on the LEMON criteria, the patient indicating a high risk for difficult to Intubations. The score was suggesting a low risk for mask ventilation difficulty. Airway management was performed using an awake intubation approach with video laryngoscopy assistance, offer a safe and effective strategy in many healthcare setting. The management of a difficult airway in patients with severe tracheal deviation due to toxic nodular goiter requires a structured anesthetic approach. Awake intubation with video laryngoscope guidance proved to be a safe and effective strategy in cases with severe anatomical distortion, particularly when spontaneous ventilation must be preserved.